Incremental integration testing of concurrent programs. - Koppol, P.V (IEEE Transactions on software engineering)
We present a method for selecting test sequences for concurrent programs from labeled transitions systems (LTS). A common approach to selecting test sequences from a set of LTSs is to derive a global LTS, called the reachability graph, and then force deterministic program executions according to paths selected from the graph. However, using a reachability graph for test path selection introduces a state explosion problem. To overcome this problem, a reduced graph can be generated using incremental reachability analysis, which consists of repeatedly generating a reachability graph for a subset of LTSs, reducing this graph, and using the reduced graph in place of the original LTSs. Unfortunately, existing incremental reachability analysis techniques generate reduced graphs with insufficient information for deterministic testing. We present an incremental approach to testing concurrent programs. Incremental testing consists of incremental reachability analysis for test path selection and deterministic testing for test execution. We define a new type of reachability graph for incremental analysis, called an annotated labeled transition system (ALTS). An ALTS is an LTS annotated with information necessary for deterministic testing. We propose practical coverage criteria for selecting tests paths from an ALTS and present an ALTS reduction algorithm. The results of several case studies are reported